The knowledge of childhood in the German Middle Ages, 1100-1350 - Schultz, James A. (James Alfred), 1947- (Middle Ages series., 1995)
The text tells stories in which abandonment, abduction, and other kinds of dislocation are commonplace, but in which children nevertheless come of age in precisely the place for which they are destined by birth. Childhood differs profoundly for males and females as it does for saintly and secular figures. Within a secular context, childhood enjoys a special status. It is shaped, elaborated, and turned into a luxury object that helps distinguish courtly culture and that anticipates more modern attitudes. The Knowledge of Childhood in the German Middle Ages, 1100-1350 provides a wealth of information for students and scholars of medieval literature, medieval history, and cultural studies.